KEWENANGAN PEMERINTAH DAERAH KABUPATEN KERINCI DALAM PENGELOLAAN PARIWISATA DANAU KERINCI - Pratiwi, Annistaesia Restu; Helmi, Helmi; Fauzani Raharja, Ivan (Fakultas Hukum Universitas Jambi, 2022)
The purpose of this research is to determine the authority of the Kerinci Regency Government in managing the tourism sector of Lake Kerinci and to find out whether the Kerinci Regency Government has prepared a master plan for tourism development. The formulation of the problem studied is about how the authority of the Kerinci Regency Government in managing the tourism sector of Lake Kerinci? and whether the development of the Master plan has been in accordance with tourism?. This research is empirical juridical, based on the results of the study it can be concluded that the tourism management carried out by the Kerinci Regency Government has not been running well. This is due to the lack of coordination between regional apparatus and the inconsistency from the government, as well as the lack of human resources according to the field of work, as well as the lack of coordination and cooperation as well as follow-up from the Jambi Provincial Government in tourism development and management. The Kerinci Regency Government already has a Tourism Master Plan and in tourism development it is also guided by the tourism master plan. However, in its implementation, several gaps were found in setting targets in the management of tourism development.